EVALUASI RESIKO K3 PADA PERAWATAN JEMBATAN TIMBANG DI PT. CAHYO PERMATA ABADI DENGAN METODE JOB SAFETY ANALYSIS - Qishas, Haechal Fachar; Putra, Al Fiillian Sah; Saputra, Muhammad Zeit Geist; Al Hafiz, Muhammad Rafi; Wirayudha, Muhammad Hafidz; Yuslistyari, Eka Indah (Jurnal Intent: Jurnal Industri dan Teknologi Terpadu, 2024)
PT Cahyo Permata Abadi is a company that provides precision measurement solutions and high-quality services for various industries by ensuring accuracy and efficiency in every project, so it is important to pay attention to the K3 aspect in the maintenance activities carried out, one of which is in the field of weighbridge maintenance services. This study aims to analyze the Occupational Safety and Health (K3) risks at PT. Cahyo Permata Abadi in weighbridge maintenance activities. The research method is Job Safety Analysis (JSA). The results of the Risk Analysis study show that several activities have significant potential hazards. In troubleshooting, there is a risk of electric shock and muscle injury with a risk value of 9. Checking the electrical system faces the risk of electric shock and short circuits with a risk value of 8. Other activities such as sensor calibration, platform cleaning, and load testing have moderate risks with potential hazards such as falling from a height, slipping, and being hit by a load. Research suggestions for risk control should be carried out through various safety measures, including the use of Personal Protective Equipment (PPE) such as insulating gloves, safety shoes, and full body harnesses. In addition, safety procedures such as Lock Out Tag Out (LOTO), warning signs, and safe work procedures are also implemented. These controls are designed to minimize potential hazards and ensure worker safety while carrying out these activities.